2022
DOI: 10.1108/jmp-04-2021-0258
|View full text |Cite
|
Sign up to set email alerts
|

How shared leadership affects team performance: examining sequential mediation model using MASEM

Abstract: PurposeThe purpose of this study is to reveal a sequential mediating process of the impact of shared leadership on team performance by studying the sequential mediating effect of team trust and team learning behavior.Design/methodology/approachThis study develops and examines a sequential mediation model using the meta-analytic structural equation modeling (MASEM) method. The sample adopted consists of 347 independent effect sizes extracted from 280 empirical papers (288 independent studies, N = 21,888 groups)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Although the positive relationship between shared leadership and team performance has been confirmed in numerous empirical studies and meta-analytic reviews (e.g. Chen et al. , 2022; Hoch and Kozlowski, 2014; Klasmeier and Rowold, 2020), research evidences suggest that shared leadership may also be harmful to team performance in certain situations.…”
Section: Dark Side Effects Of Shared Leadershipmentioning
confidence: 98%
See 2 more Smart Citations
“…Although the positive relationship between shared leadership and team performance has been confirmed in numerous empirical studies and meta-analytic reviews (e.g. Chen et al. , 2022; Hoch and Kozlowski, 2014; Klasmeier and Rowold, 2020), research evidences suggest that shared leadership may also be harmful to team performance in certain situations.…”
Section: Dark Side Effects Of Shared Leadershipmentioning
confidence: 98%
“…Ali et al, 2020;Gu et al, 2022) and improving team or organizational performance (e.g. Chen et al, 2022;D'Innocenzo et al, 2021). In addition, some recent meta-analyses have identified the unique effect of shared leadership in explaining the variance in team performance when compared with the traditional vertical leadership (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organizations increasingly rely on work teams to perform more complex, non-routine and uncertain tasks to maintain a competitive advantage (Chen et al, 2022;Sinha et al, 2021). With knowledge workers in such teams desiring for more autonomous and meaningful work, scholars have suggested that traditional vertical leadership which is referred to as formal hierarchical leadership projecting downward influences on followers might not be the most effective under these circumstances (Bligh et al, 2006;Klasmeier and Rowold, 2022;Pearce, 2004).…”
mentioning
confidence: 99%
“…With knowledge workers in such teams desiring for more autonomous and meaningful work, scholars have suggested that traditional vertical leadership which is referred to as formal hierarchical leadership projecting downward influences on followers might not be the most effective under these circumstances (Bligh et al, 2006;Klasmeier and Rowold, 2022;Pearce, 2004). And shared leadership, which is defined as the dynamic, lateral and interactive influence process among team members as they take on leadership responsibilities together to lead one another to achieve team goals (Pearce and Conger, 2003), is essential for team performance (Chen et al, 2022;Song et al, 2020).…”
mentioning
confidence: 99%